Perancangan Sistem Informasi Akuntansi Persediaan Bahan Baku Kain Hasil Maklon Berbasis Web Pada Perusahaan Manufaktur - Kristina Lena Owa; Karyadi Karyadi; Falaah Abdussalaam (LPPM UBHINUS MALANG, 2023)
The recording system for supplies of raw materials made of Maklon fabrics at PT. Leading Garment Industries is still done manually. Therefore, the resulting information report is inaccurate and takes a long time to produce a raw material report. The purpose of this research is to help manage and separate the data from the inventory of other raw materials and raw materials for fabric produced by Maclon appropriately and accurately. In this study, qualitative research methods are used with a descriptive approach. Data collection methods include observations, interviews, and case studies. The development system used is the waterfall method. Maklon's raw material inventory information system is designed for the Web with the PHP programming language and MySQL database. Based on the results of the research, the author will create an information system for Maklon raw materials and fabric inventory in the manufacturing company. Test results conclude that the designed system has been successful and in line with what was desired. The establishment of an accounting information system for raw material supplies will help in the processing of data and the provision of information reports for raw material supplies required by the related departments in the manufacturing company.